Struktur Kekuasaan Percakapan di Platform Instagram Terkait Keterlibatan Prabowo dalam Dewan Perdamaian - Najwa Aisyah Salsabila; Lintang Prameswari; Vania Areta Pitra Safa; Celvin Dwi Putra Mudianto; Linggar Apritataqwa Giandivari; Inas Yumna Depryananda (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Prabowo Subianto’s involvement in the Board of Peace for post-conflict reconstruction in Gaza generated extensive public discussion on Instagram and raised questions about whether the observed uniformity of opinion emerged organically or reflected structural communication dynamics. This study examined the conversation network, identified dominant actors, and analyzed the distribution of communicative power using a quantitative big-data approach based on Social Network Analysis (SNA). Data comprised 41,552 interactions connecting 35,490 Instagram accounts collected between January 22 and March 18, 2026, and analyzed with NodeXL Pro, while sentiment was measured using the InSet lexicon. The findings revealed a semi-fragmented network consisting of three major clusters representing national politics, international peace, and public accountability. A clear distinction emerged between the center of attention and the center of power, with @prabowo attracting discussion while media and information accounts controlled information flows through brokerage positions. Negative sentiment accounted for 81% of interactions, indicating that public opinion was reinforced through networked power rather than purely organic participation.